Támadás Fiume autonómiája ellen : a fiumei Közigazgatási Bizottság 1897. évről készült jelentése nyomán - Simonné Pallós, Piroska (Közép-Európai Közlemények, 2013)
Throughout the course of history, Fiume belonged to the Hungarian Crown three times. The Hungarian rule seemed ideal for the citizens, because they hoped for economic growth and respect for their rights. For decades their relationship seemed good, however in the 1890s there was a turnaround. There were a lot of problems behind the conflicts: economic woes, the strengthening of Italian irredentism, the different national interests, social tensions, differences in language and mentality – and the growing Magyarization policy, followed by the gradual degradation of Rijeka’s autonomy, then the irreversible and permanent deterioration of the relationship. This process is being revealed and depicted in the report made by the Administrative Committee of Fiume from the year 1897.